Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1021/bi00587a016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid preparation of mitochondrial malate dehydrogenase from rat liver and heart

Abstract: Mitochondrial malate dehydrogenase (L-ma-1ate:NAD' oxidoreductase, EC 1.1.1.37) has been purified from both rat liver and rat heart by using Sepharose-Blue Dextran pseudoaffinity chromatography. Under the conditions employed most of the mitochondrial malate dehydrogenase and some cytosolic malate dehydrogenase are adsorbed, whereas many proteins simply pass through. The blue column is then subjected to several treatments which elute a variety of other proteins (notably residual cytosolic malate dehydrogenase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Mitochondrial malate dehydrogenase was purified from rat hearts obtained from 150-g male Sprague-Dawley rats. Pure enzyme was obtained after ammonium sulfate precipitation from a crude homogenate and consecutive chromatography on (carboxymethyl)-Sepharose, blue Sepharose, and 5'-AMP-Sepharose as previously described (Glatthaar et al, 1974;Kuan et al, 1979). Sixty-six milligrams of mMDH with a specific activity of 183 units/mg was obtained from 400 g of rat hearts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial malate dehydrogenase was purified from rat hearts obtained from 150-g male Sprague-Dawley rats. Pure enzyme was obtained after ammonium sulfate precipitation from a crude homogenate and consecutive chromatography on (carboxymethyl)-Sepharose, blue Sepharose, and 5'-AMP-Sepharose as previously described (Glatthaar et al, 1974;Kuan et al, 1979). Sixty-six milligrams of mMDH with a specific activity of 183 units/mg was obtained from 400 g of rat hearts.…”
Section: Methodsmentioning
confidence: 99%
“…To this solution, a 5-fold molar excess of dithiothreitol 1 Abbreviations: NAD+, oxidized nicotinamide adenine dinucleotide; mMDH, mitochondrial malate dehydrogenase; sMDH, cytoplasmic malate dehydrogenase; MDH, malate dehydrogenase; LDH, lactate dehydrogenase; HPLC, high-performance liquid chromatography; TPCK, TV-tosyl-L-phenylalanine chloromethyl ketone; SDS, sodium dodecyl sulfate; TFA, trifluoroacetic acid; PTH, phenylthiohydantoin; Tris, tris(hydroxymethyl)aminomethane. was added relative to the estimated cysteine content (Kuan et al, 1979). The reduction reaction was incubated for 3 h at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Marangos and Constantinides [22] have shown multiple forms of glyceraldehyde-3-phosphate dehydrogenase on electrofocusing and suggested that these could arise from distinct conformational forms of a multimeric enzyme composed of a single subunit type. Alternatively, Kuan et al [23] have proposed that multiple forms of mitochondrial malate dehydrogenase seen in isoelectric focusing may arise through masking of ionic side-chain groups by tightly bound phospholipid. Further work is necessary to decide which, if any, of the above explanations applies in the case of the multiple forms of aldchyde dehydrogenase.…”
Section: Isoelectric Focusingmentioning
confidence: 99%
“…The mitochondrial MDH activity was found to have a pH optimum of 9.3-9-5 using Tris/HCI and bicarbonate buffers in assays over a pH range of 7-10. This was much higher than the pH optimum (6.5-7.5) reported from other sources (Flury et al, 1974;Kuan et al, 1979). Both thyroxine and hydroxymalonate inhibited the M D H activity.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 55%